2008
DOI: 10.2989/ajar.2008.7.3.4.651
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between VCT and HIV/AIDS treatment uptake: perspectives from a mining-sector workplace in South Africa

Abstract: This qualitative study sought to understand users' perceptions of the voluntary counselling and testing (VCT) and HIV-treatment services offered by a mining company in South Africa, with the intention of making recommendations to improve the rates of uptake. A purposive sample of 75 employees was interviewed and three focus groups were conducted with VCT users as well as with HIV-positive employees currently enrolled in the company's treatment programme. The relatively high uptake of VCT at the workplace appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 0 publications
2
66
0
Order By: Relevance
“…However the literature reviewed and our interviews suggest that assessing whether a workplace will have better results by testing on-or off-site is a complex issue. A corporate decision about on-site testing will depend on the capacity to uphold confidentiality surrounding test results and ensure that presenting for testing will not result in stigmatization (Bhagwanjee, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However the literature reviewed and our interviews suggest that assessing whether a workplace will have better results by testing on-or off-site is a complex issue. A corporate decision about on-site testing will depend on the capacity to uphold confidentiality surrounding test results and ensure that presenting for testing will not result in stigmatization (Bhagwanjee, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, workplaces must ensure that workers are not coerced or pressured into being tested-an issue illuminated in Bhagwanjee et al's (2008) study of VCT in a South African mine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Connelly and Rosen (2006), in terms of the number of employees in DMPs only 12.2% of mineworkers were enrolled in workplace ART programmes, despite 90% of these mineworkers having had access to ART. At the site of the study that is being reported on, Bhagwanjee, Petersen, Akintola and George (2008) found a relatively low uptake rate into the mine's ART programme, despite an uptake rate of 86% achieved in the 2007 VCT campaign. Significant obstacles emerged in interviews with employees that hindered them from enrolling in the mine's ART programme.…”
Section: Introductionmentioning
confidence: 91%